Inventarisasi Tumbuhan Obat di Desa Pelangsian Kecamatan Mentawa Baru Ketapang Kabupaten Kotawaringin Timur: Inventory of Medicinal Plant in Pelangsian Village Mentawa Baru Ketapang Subdistrict Regency of East Kotawaringin - Nurul Qamariah; Evi Mulyani; Nurmila Dewi (Borneo Journal of Pharmacy, 2018)
Indonesia is a large archipelagic country and it is a tropical country with a huge variety of plants. Borneo as one of five major islands has tropical rainforest with a high level of plants diversities in the world. Traditional treatment by medicinal plants is still used by the people in Pelangsian village. The purpose of this study was to find out how the way the people in Pelangsian village use the traditional medicines, also about the type and the benefits of medical plants there, and which parts of the plants that used to be the traditional medicines. This research uses the descriptive method with a qualitative approach, data collecting is done by making an observation and interviews. Sampling in this research used purposive sampling technique in order to determine key informant with criteria that have been determined by the researcher and snowball sampling that determines the next informant who has already recommended by the key informant before. The result of the research was there are 52 species of medicinal plants that have been determined, the leaves, trunks, peels, fruit, seeds, roots, woods, rhizomes, are the parts of the plants that usually used by the people there and the way to use those herbs is boiled, stacked, rubbed and consumed directly.